Kelemahan Kedudukan Pembuktian Keterangan Anak Korban Dalam Perkara Asusila: - Muammar, Muammar; Meldandy, Maulana; Sardari, Ahmad Asif (Al-Mizan (e-Journal), 2024)
The weak position of witness testimony of child victims of indecent crimes, due to the position of witness testimony of child victims cannot be fully accounted for in the criminal justice system. This article aims to describe the weak position of witness testimony of child victims of indecent crimes and the reasons for the unreliability of witness testimony of child victims of indecent crimes. This research is based on qualitative research by conducting a study of legislation, court decisions and literature studies. The results showed that the witness testimony of child victims of indecent acts is not considered valid evidence, but still has value as a clue. Article 188 paragraph (1) of the Criminal Procedure Code, the testimony of a child witness who is not sworn can be used as a clue even though it does not fulfil the formal requirements of evidence. In Supreme Court Decision Number 3913 K/Pid.Sus/2019, it is stated that child witness testimony, although it does not have full evidentiary power because it is not sworn, is still considered to strengthen other evidence. To fulfil the minimum requirement of two pieces of evidence, child witness testimony must be supported by other valid evidence. Therefore, the criminal justice system needs to give special treatment to child witness testimony in immoral cases so that it remains valuable in evidence.